Analysis of the Influence of Upper Protective Layer Mining on the Effect of Pressure Relief and Protection of Coal and Rock Masses between the Lower Overburden Layers - Jiaxin Dang (Hindawi Limited, 2021)
Protective seam mining is an effective gas pressure relief method in deep mining. Effective theoretical calculation methods in the current studies on the prediction of pressure relief protection effect of interbed coal and rock masses and their distribution laws are lacking. Thus, the evaluation and research with respect to pressure relief effect in protective seam mining relatively lag behind. This situation restricts the engineering feasibility evaluation and decision making in the protective seam mining. Therefore, the influence of upper protective seam mining on the pressure relief protection effect of coal and rock mass between underlying beds was investigated in this study. On the basis of an analysis of concrete engineering projects, a mechanical model was constructed for the pressure relief protection effect of upper protective seam mining on the coal and rock mass between underlying beds. The distribution equation of pressure relief expansion ratio in the underlying protected seam was also derived. The influence laws of main influencing factors on the pressure relief protection effect of the protected seam were revealed as well. In the end, the pressure relief effect was analyzed and verified for the protected seam before and after mining through numerical simulation and similarity simulation test. The pressure relief effect of upper protective seam mining on the coal and rock mass between underlying beds and the distribution characteristics were deeply explored in this study, which could provide a theoretical reference for the decision making in the gas extraction engineering design and pre-evaluation of extraction effect. Results show that the effective pressure relief zone (expansion rate>0.3%) of the protected seam beneath the goaf is located within the range of approximately 40 m from the coal wall to the rear part. It also presents an approximate “Λ-shaped distribution characteristic,” that is, it experiences migration and evolution with the advancement in the working face. Moreover, the peak pressure relief lags behind the coal wall on the working face by nearly 10–20 m. In the numerical simulation, the expansion ratio in the goaf also presents an approximate “Λ-shaped distribution.” Its effective pressure relief zone is the 50 m range from the coal wall to the rear part of the goaf, and the peak value lags behind the coal wall by around 15 m. The theoretical results and numerical simulation results are basically consistent with the physical experiment results. The expansion rates are 1.25%, 1.268%, and 1.32%, respectively. The elastic modulus E of coal seam and interbed spacing H are the main influencing factors of the swelling deformation and are negatively correlated with the expansion ratio. In the actual mining process, E and H of the protected layer can be measured to infer the expansion deformation of the protected layer.